2019
DOI: 10.26479/2019.0502.33
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Justicia gendarussa (Burm) f. is one of the common, well known and important medicinal shrub. Justicia gendarussa (Burm) f. plant leaves medicinal properties such as, anti arthritic, anti-inflammatory and immunosuppressive activities and also this plant to cure many diseases. Ethanol and aqueous extract of the dry plant leaves were collected and qualitatively analyse the phytochemical compounds. Silver nano particles (AgNPs) were synthesised biologically from the aqueous extract of the Justicia gendarussa (Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Another study by Ahmed et al [ 34 ] also reported spherical AgNPs with a diameter of 34 nm when Azadirachta indica extract was used as the reducing and stabilizing agent. Irregular spherical shape and size between 20 and 100 nm was described in a study by Vijayakumar [ 35 ], where Justicia gendarussa extract was used for the phytofabrication of AgNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Ahmed et al [ 34 ] also reported spherical AgNPs with a diameter of 34 nm when Azadirachta indica extract was used as the reducing and stabilizing agent. Irregular spherical shape and size between 20 and 100 nm was described in a study by Vijayakumar [ 35 ], where Justicia gendarussa extract was used for the phytofabrication of AgNPs.…”
Section: Discussionmentioning
confidence: 99%